Create a Mathematical Model to Estimate the Weight of Iraqi Fetuses Using Ultrasound Images - A. Hussain, Ahlam; F. Kanger, Ebtesam (International Journal of Psychosocial Rehabilitation, 2020)
Background: Ultrasound (US) imaging is a medical imaging technique considered one of the most used techniques in hospitals and clinical centers around the world due to its being safe, economical, transferable, and adaptable. US imaging is used to diagnose human body parts and their functions. The most common use of US in pregnancy is to monitor the developments of fetuses and reveal abnormalities, estimate gestational age (GA), and estimate fetal weight (EFW). EFW is an important component of maternity health care, especially in the management and planning of the delivery mode. This will play a major role in newborn and maternal safety. EFW depends on the measurement of fetal biometry, such as abdominal circumference (AC), femur length (FL), bi-parietal diameter (BPD), and others. Accurate measurement of fetal biometry depends on the experience of sonographers. There are several models that were used to estimate fetal weight (EFW) depending on one or more biometrics of fetuses, but these models still give some errors in EFW in Iraq. So, this study has been carried out for creating the first EFW model for the first time in Iraq and the Middle East; a study is conducted to determine the weight of the fetus by finding a special mathematical model for the Iraqi fetuses. Depending on the US images taken from Iraqi hospitals, as will be explained in this search. Methods: This study was performed in the department of Obstetrics and Gynecology in Al-Yarmouk Teaching Hospital and Al-Alawiya Teaching Hospital in Baghdad, Iraq, during 2019 on 200 pregnant women with singleton and normal pregnancies, fetal GA (36-40) weeks (W), and the last US scan was less than 7 days before birth. The obtained dataset (fetal biometry and actual birth weight (ABW)) was utilized to develop EFW using the IBM SPSS Version 23 software package (software). Results: Statistical analysis indicated that there was a significant difference between the ABW and EFW using most weight estimation models. Only our proposed model and the Hadlock2 model produced acceptable results, where the correlation between ABW and EFW by the proposed model was R = 0.964 and by the Hadlock2 model was R = 0.920, while it extremely declined when using other models and showed less correlation. By using the Hsieh model, R=0.330; by using the Woo model, R=0.236; and by using the Jordaan model, R=0.667. Conclusion: The proposed model and Hadlock2 model produce results better than other models in EFW for Iraqi pregnant women, but depending on the absolute mean error (AME), absolute percentage error (APE), and R value, we conclude that the proposed model was the best model for EFW in Iraq and gave the most acceptable results compared with ABW.